The Rationality of Official Intervention in the Forward Exchange Market - Stein, Jerome L. (Quarterly Journal of Economics, 1963)
I. Fighting speculative flurries, 312. — II. Living with a deficit on the basic balance, 314. — III. Conclusion, 316.